Formative peer assessment in healthcare education programmes: protocol for a scoping review. Issue 11 (8th November 2018) - Stenberg, Marie; Mangrio, Elisabeth; Bengtsson, Mariette; Carlson, Elisabeth
Abstract : Introduction: In formative peer assessment, the students give and receive feedback from each other and expand their knowledge in a social context of interaction and collaboration. The ability to collaborate and communicate are essential parts of the healthcare professionals' competence and delivery of safe patient care. Thereby, it is of utmost importance to support students with activities fostering these competences during their healthcare education. The aim of the scoping review is to compile research on peer assessment presented in healthcare education programmes, focusing formative assessment. The result of the scoping review will form the basis for developing and conducting an intervention focusing collaborative learning and peer assessment in a healthcare education programme. Methods and analysis: The scoping review will be conducted by using the framework presented by Arksey & O'Malley and Levac et al . The primary research question is: How are formative peer assessment interventions delivered in healthcare education? The literature search will be conducted in the peer-reviewed databases PubMed, Cumulative Index to Nursing and Allied Health Literature, Education Research Complete and Education Research Centre between September and December 2018. Additional search will be performed in Google Scholar, hand-searching of reference lists of included studies and Libsearch for identification of grey literature. Two researchers will independently screen title and abstract. Full-text articles will be screened by three researchers using a charting form. Studies meeting the inclusion criteria will be critically evaluated using the Critical Appraisal Skills Programme. A flow diagram will present the included and excluded studies. A narrative synthesis will be conducted by using thematic analysis as presented by Braun and Clarke. The findings will be presented under thematic headings using a summary table. To enhance validity, stakeholders from healthcare education programmes and healthcare institutions will be provided with an overview of the preliminary results. Ethics and dissemination: Research ethics approval is not required for the scoping review.